Comparative study of soft thermal printing and lamination of dry thick photoresist films for the uniform fabrication of polymer MOEMS on small-sized samples. (12th April 2017) - Abada, S; Salvi, L; Courson, R; Daran, E; Reig, B; Doucet, J B; Camps, T; Bardinal, V
Abstract: A method called 'soft thermal printing' (STP) was developed to ensure the optimal transfer of 50 µ m-thick dry epoxy resist films (DF-1050) on small-sized samples. The aim was the uniform fabrication of high aspect ratio polymer-based MOEMS (micro-optical-electrical-mechanical system) on small and/or fragile samples, such as GaAs. The printing conditions were optimized, and the resulting thickness uniformity profiles were compared to those obtained via lamination and SU-8 standard spin-coating. Under the best conditions tested, STP and lamination produced similar results, with a maximum deviation to the central thickness of 3% along the sample surface, compared to greater than 40% for SU-8 spin-coating. Both methods were successfully applied to the collective fabrication of DF1050-based MOEMS designed for the dynamic focusing of VCSELs (vertical-cavity surface-emitting lasers). Similar, efficient electro-thermo-mechanical behaviour was obtained in both cases.